The frequency of bone fractures among patients with chronic kidney disease not on dialysis: two-year follow-up - Figurek Andreja; Vlatkovic Vlastimir; Vojvodic Dragan; Gasic Branislav; Grujicic Milorad (Sciendo, 2017)
Introduction. Renal osteodystrophy is a severe complication of chronic kidney disease (CKD) that increases morbidity and mortality in these patients. Mineral and bone disorder starts early in CKD and affects the incidence of bone fractures. The aim of this study was to observe the frequency of diverse bone fractures in patients with CKD not on dialysis.